A study of the IR spectra of the copigments of malvin chloride with organic acids - ZORAN P. NEDIC; JELISAVETA M. BARANAC; JASMINA M. DIMITRIC-MARKOVIC; UBAVKA B. MIOC (Journal of the Serbian Chemical Society, 2001)
The infrared spectra of the copigments of malvin with several organic acids: caffeic, ferulic, sinapic, chlorogenic, and tannic, were analyzed in order to elucidate the bonding of the molecules in the copigments. It was established that copigmentation is realized through hydrogen bonding between malvin molecules and the acids under study. The infrared spectra reveal that two groups of hydrogen bonds are formed, which include interactions of different molecular structures: hydroxy groups (bands around 3500 cm1) and oxonium ions of the molecules (bands below 3000 cm1). The formed hydrogen bonds were found to be of different strengths. The strengths of the hydrogen bonds were tentatively correlated with thermodynamic properties of the corresponding copigmentation reactions.